Ultrasonic Velocity Profiler for the Measurement of a Bubbly Flow Velocity Vector in Small Channels - Wongsaroj, Wongsakorn; Takahashi, Hideharu; Thong-un , Natee; Chanwutitum, Jirasak; Kikura, Hiroshige (International Journal of Integrated Engineering, 2023)
The multi-dimensional velocity distribution of coolant in bubbly flow within the fuel rod bundles of the reactor core in boiling water reactors (BWRs) is elucidated by experimental investigation in this study. Since a measurement technique is required for such an investigation, this paper proposes the development of an ultrasonic velocity profiler (UVP). The combination of special ultrasonic transducers and modified signal processing on the UVP is proposed to obtain a multi-dimensional velocity vector of the bubbles and liquid in bubbly flow. The ability of the proposed technique is demonstrated by performing an experiment in swirling bubbly flow and its applicability confirmed by comparing the results with another technique. The sound pressure distribution in the narrow channel of the rod bundle is then measured prior to the verification of the ultrasonic wave emitted through a small channel. The echo signal reflected from reflectors dispersed in the liquid, bubble, and tracer particles in the small channel of the rod bundle indicates that the proposed UVP can be applied in this application with a low level of multi-reflection. Finally, the UVP system is demonstrated to measure the velocity vector of bubbly flow in the narrow flow channel on the rod bundle, and the velocity vector of the bubble and liquid obtained simultaneously.